2021
DOI: 10.3847/1538-3881/abfc53
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Study and Absolute Parameter Estimation of Six Totally Eclipsing Contact Binaries

Abstract: High precision CCD observations of six totally eclipsing contact binaries were presented and analyzed. It is found that only one target is an A-type contact binary (V429 Cam), while the others are W-type contact ones. By analyzing the times of light minima, we discovered that two of them exhibit secular period increase while three manifest long-term period decrease. For V1033 Her, a cyclic variation superimposed on the long-term increase was discovered. By comparing the Gaia distances with those calculated by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 241 publications
2
53
0
Order By: Relevance
“…We carried out a project on the analysis of ELMRCBs. Statistical and simulation studies have indicated that the photometric mass ratios are consistent with the spectroscopic ones for totally eclipsing contact binaries (Rucinski 2001;Pribulla et al 2003;Terrell & Wilson 2005;Li et al 2021b). Rucinski (2001) determined the relationship between the maximum amplitude, the mass ratio, and the contact degree for contact binaries, and found that the smaller the amplitude, the smaller the mass ratio.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…We carried out a project on the analysis of ELMRCBs. Statistical and simulation studies have indicated that the photometric mass ratios are consistent with the spectroscopic ones for totally eclipsing contact binaries (Rucinski 2001;Pribulla et al 2003;Terrell & Wilson 2005;Li et al 2021b). Rucinski (2001) determined the relationship between the maximum amplitude, the mass ratio, and the contact degree for contact binaries, and found that the smaller the amplitude, the smaller the mass ratio.…”
Section: Introductionmentioning
confidence: 73%
“…The relationship between the mean residual and mass ratio q is shown in Figure 1. It is clearly seen that all the q − search curves have very deep and sharp minima, indicating very precise mass ratio can be obtained (e.g., Zhang et al 2017;Li et al 2019Li et al , 2021bTerrell 2022). The mass ratio corresponding to the minimum of the mean residual was chosen as the initial value and an adjustable parameter, new solutions were started to obtain a convergent result, then the errors of mass ratio can be determined.…”
Section: Light-curve Investigationmentioning
confidence: 99%
“…Terrell & Wilson (2005) showed that the photometric mass ratio accuracy decreases as the system geometry changes from full eclipse to partial eclipse. Among 101 systems (59 total eclipsing and 42 partially eclipsing) collected by Li et al (2021), almost half of the partial eclipsing binary photometric mass ratios were found to differ from the ones determined from RV curves. The mismatch was as big as 0.4 in some cases where the orbital inclination angle was less than 70 • .…”
Section: Resultsmentioning
confidence: 88%
“…The primary component of TIC 0349294422 is bigger as well as hotter, which suggests TIC 0349294422 is an A-subtype system, and the bigger component of TIC 0155968973 is cooler, suggesting that TIC 0155968973 is a W-subtype one. Thus they may be formed from distinct formation channels (e.g., Li et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the diagram of log L−log T in Figure 8, we can see that both components of detached binaries are within or very close to the MS band (the area between ZAMS and TAMS). In the log R −log M and log L−log M diagrams, the more massive primary of the W UMa-type contact binary TIC 0349294422 is close to the ZAMS, while its less massive secondary is out of TAMS, which indicates that the more massive primary in the binary should be less evolved than the less massive secondary (e.g., Yakut & Eggleton 2005;Li et al 2021). The detached system TIC 0122446076 may begin to leave the TAMS since the primary and the secondary are located on the TAMS loci in all the diagrams.…”
Section: Discussionmentioning
confidence: 99%